Anger and creative process engagement: The moderating effects of social context - Costa, C. G.; Zhou, Q.; Ferreira, A.I. (Academy of Management Proceedings, 2015)
Drawing on the componential model of creativity and the interactionist perspective, this paper hypothesized and tested the relationships between anger and three sub-processes of creative process (i.e. problem identification, information search and encoding and idea generation) and the moderating influence of social context (namely, co-worker support versus relationship conflict) on those relationships. The hypothesized model was tested with daily survey data obtained from a sample of 98 employees (422 days) from three consultancy companies in Portugal. Results of hierarchical linear modelling (HLM) analysis revealed that anger was positively related to problem identification but unrelated to informational searching and encoding and idea generation. However, anger was negatively related to information searching and encoding and idea generation when co-worker support was low or relational conflict was high but positively related to information searching and encoding when co-worker support was high rather than low.